Corporate governance, firm operating performance and equity returns : evidence from Asia. - Mok, Alastair Marcus Kok Jen. (2008)
Our study examines the relationship between corporate governance and Asian firms’ equity returns and operating performance. We documented evidence of corporate governance ratings’ predictive power in predicting firms’ future operating performance, as measured by ROA, over a number of years. Furthermore, some sub-indices of the overall firm corporate governance ratings actually have higher predictive power as compared to the overall firm corporate governance ratings. However, the evidence on firms’ equity returns is not conclusive across Asian economies. Some countries’ dictatorship portfolio, which we used as a proxy for poorly governed firms, exhibit positive abnormal returns over the sampling period. This contradicts past researches’ findings. A small sample size, a lack of corporate governance data and difference in research methodology might be possible reasons for this phenomenon observed. However, from the empirical evidence documented in our study, the relationship between corporate governance and equity returns is inconclusive and requires more in-depth examination in future research.